Applications of Microfluidics in Quantitative Biology. Issue 5 (27th October 2017) - Bai, Yang; Gao, Meng; Wen, Lingling; He, Caiyun; Chen, Yuan; Liu, Chenli; Fu, Xiongfei; Huang, Shuqiang
Abstract : Quantitative biology is dedicated to taking advantage of quantitative reasoning and advanced engineering technologies to make biology more predictable. Microfluidics, as an emerging technique, provides new approaches to precisely control fluidic conditions on small scales and collect data in high‐throughput and quantitative manners. In this review, the authors present the relevant applications of microfluidics to quantitative biology based on two major categories (channel‐based microfluidics and droplet‐based microfluidics), and their typical features. We also envision some other microfluidic techniques that may not be employed in quantitative biology right now, but have great potential in the near future. Abstract : Microfluidics, as an emerging technique, provides new approaches to precisely control fluidic conditions on small scales and collect data in high‐throughput and quantitative manners. In this review, the authors present the relevant applications of microfluidics to quantitative biology based on two major categories (channel‐based microfluidics and droplet‐based microfluidics), and their typical features. All these features meet the requirements of quantitative biology that dedicates to make biology more predictable.